Integrating Good Governance, Integrity Zone, and Digitalization: A Synergistic Model for Immigration Service Reform in Indonesia - Astuti, Rita Kusuma; Wirdhiningsih, Virra; Pujonggo, Seno Setyo; Jannah, Rahmawati Nurul; Maulidia, Hanifa; Priyatno, Mas Budi; Febrianto, Arief (Jurnal Manajemen Pelayanan Publik, 2026)
Public service reform in sensitive sectors like immigration requires a balance between sovereignty control and service excellence. This study aims to develop an effective reform model by synthesizing three strategic pillars: Good Governance (GG), the Integrity Zone (IZ) program, and Digitalization. Utilizing a qualitative policy synthesis and thematic analysis of institutional data (LKjIP 2024) and longitudinal records (2018-2024), the research evaluates the implementation trajectory of 103 immigration units in Indonesia. The findings reveal a "Compliance-Performance Gap," where structural certification under the IZ program does not always result in a total cultural mindset shift. However, digitalization emerges as a critical "technical enforcer" that locks integrity into the system by eliminating face-to-face discretion. The study proposes an Integrated Reform Model where GG provides the normative foundation, IZ provides the structural mandate, and Digitalization acts as the technical engine. This synergy ensures that the dual mandate of immigration—securing borders while facilitating public welfare—is achieved through transparent, accountable, and non-discretionary processes. The model provides a strategic blueprint for other public institutions facing complex bureaucratic challenges in emerging economies.